The Role of Villages in Stunting Prevention - Halu, Silfia Angela Norce; Banul, Maria Sriana; Nanur, Fransiska Nova; Dafiq, Nur; Narut, Yosef Firman (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2025)
The number of designated stunting-priority locations in Manggarai Regency has increased each year, according to local government determinations. Data show that out of 188 villages/sub-districts in Manggarai Regency, 97 have achieved stunting-free status. This study aimed to explore the role of villages in addressing stunting in Manggarai Regency. This research employed a qualitative analytical design using a phenomenological approach. The informants included village heads, parents of stunted toddlers, and village midwives. A purposive sampling technique was used. Data were collected through non-participant observation and in-depth interviews. The role of villages in stunting prevention involves policy regulations established at the central, provincial, and district levels. The allocated budget is sourced from village funds in accordance with government policies. However, healthcare resources remain limited. The availability of transparent data enables evidence-based interventions. Policies, budget allocations, human resources, and data serve as the main foundation for stunting reduction efforts.